A fluorescent probe for a lewisite simulant. (29th September 2016) - Lee, Doo-Hee; Lee, Dong-Nam; Hong, Jong-In
Abstract : A fluorescent probe showed high selectivity and sensitivity for an organoarsenic blister agent simulant, arsenic trichloride. Abstract : Herein, we report for the first time a highly sensitive fluorescent probe for the detection of an organoarsenic blister agent simulant, arsenic trichloride (AsCl3 ). This probe showed high selectivity to AsCl3, in the presence of other metal ions, even at low concentrations. Moreover, quantitative determination of AsCl3 in soil was achieved with a detection limit of 61.2 μmol kg −1 that is sufficiently lower than the reported LD50 of lewisite.